Integrasi Good Attitude dan Excellent Service dalam Mewujudkan Good Government Governance - Rahman, Sundari; Musmulyadi (Institut Agama Islam Negeri Parepare, 2021)
The economic crisis that hit Indonesia in mid-1997 and also pressure from the community to encourage the government to adopt policies for the realization of a just, prosperous, and prosper. In order to realize the wishes of citizens who continue to urge the government then pursued one way by implementing good government governance. Good governance covers broad aspects of life ranging from legal, political, economic, and social as well as closely with the principal task of organizing the function of state power executive, legislative, and judicial branches. Government in making all aspects related to it, the government tried to create a governance system of government based on excellent service that is supported by both the behavior or attitude of the implementing agency. Good attitude in this regard reflects the personality and attitude of high responsibility of state officials in performing its duty of providing excellent service to the community. Excellent service which became a major cornerstone in restoring the government's image in the public eye particularly in view of the terms of service should be carried out to the maximum so that people's expectations of the government can be realized.